The Benefits of Using Innovative Technology In Improving Engineering Culture of University Students - Yulchieva, Zulfizarkhon; Mustafaeva, Inobat (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the preparation of engineering university students for production new practices based on innovative technology, implementation in the educational process of practical versions of innovative multifunctional virtual enterprises for students of an engineering university.